Characteristics of Nursing training in the Family Health Strategy of a Microregion of Health in Ceará (Research, Society and Development, 2020)
The study aimed to describe the characteristics of the training of nurses in the Family Health Strategy of a microregion of health in Ceará. Exploratory research, under the quantitative approach, based on a case study, developed from July to September 2019, with 64 nurses of the 12th Health Regional of Ceará. The collection took place through a Google Forms® questionnaire and the data were analyzed using R software. Most nurses studied Nursing at a private institution (62.5%); as for the course modality, there was a predominance of two, integral and morning, 42.2%, respectively; 15.6% studied or are studying another graduation; 25% attended nursing assistants or technicians. The research data allow us to subsidize the construction of public policies based on the local reality, for professional development and the Unified Health System at the regional level.